2013
DOI: 10.1177/0883911512473230
|View full text |Cite
|
Sign up to set email alerts
|

Self-cross-linkable hydrogels composed of partially oxidized alginate and gelatin for myocardial infarction repair

Abstract: Calcium cross-linked alginate hydrogel has shown positive results for the treatment of myocardial infarction in both acute and chronic rat models. However, cross-linked alginate hydrogels possess poor mechanical properties, uncontrollable degradation, and poor cell adhesion and infiltration. In this study, covalent cross-linking of partially oxidized alginate and gelatin hydrogel was developed for myocardial infarction treatment, as compared to cross-linked alginate hydrogel and saline. Specifically, the gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Our previous study showed that the covalent cross-linking of gelatin with alginate forms a hydrogel with both enhanced mechanical properties and bioactive motifs for cell attachment, biodegradability, and functional recovery. 26 In the current study, we developed a novel hybrid hydrogel system with chemically encapsulated gelatin NPs, which are pH sensitive, for the sustained co-delivery of BIO + IGF-1 in MI treatment. The oxidation of sodium alginate produced aldehyde groups, which can form unstable amines found within the free amino group in the gelatin NPs; thus, they covalently linked the NPs to the alginate polymer chain.…”
Section: Development Of a New Hybrid Hydrogel Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that the covalent cross-linking of gelatin with alginate forms a hydrogel with both enhanced mechanical properties and bioactive motifs for cell attachment, biodegradability, and functional recovery. 26 In the current study, we developed a novel hybrid hydrogel system with chemically encapsulated gelatin NPs, which are pH sensitive, for the sustained co-delivery of BIO + IGF-1 in MI treatment. The oxidation of sodium alginate produced aldehyde groups, which can form unstable amines found within the free amino group in the gelatin NPs; thus, they covalently linked the NPs to the alginate polymer chain.…”
Section: Development Of a New Hybrid Hydrogel Systemmentioning
confidence: 99%
“…Both the labeled gelatin NPs alone, as well as the labeled gelatin NPs that conjugated to the hydrogels, were injected into the area affected by MI in 20 rats (ten rats in each group), as described in a previous study. 26 The fluorescence of both groups was examined and recorded by an in vivo imaging system (DXS 4000 PRO; Eastman Kodak Co, Rochester, NY, USA) every 5 days.…”
Section: Drug-releasing Profile In Vitro and In Vivomentioning
confidence: 99%
See 3 more Smart Citations